Sex, ethnicity and the professions in West Malaysia: some preliminary considerations - O'Brien, Leslie N. (Universiti Kebangsaan Malaysia, 1979)
It is postulated that in Malaysia there are class, sex and ethnic differentials in such life chances as access to higher education, as well as in options and opportunities to utilize this education. Class, sex and ethnicity are seen here as independent but interacting variables. This paper examines the extent to which sex is a significant variable for understanding social stratification in West Malaysia. The influences of class and ethnicity will be referred to where necessary.